Sistem Smart Trash Berbasis Long Range Menggunakan Metode Research And Developmen (R&D) - Syahru Romadhona, Muhammad; Mardi Yudhi Putra (Jurnal Manajemen Informatika & Teknologi, 2026)
Conventional waste management at SMK PKP 1 Jakarta is inefficient due to the lack of sorting and real-time capacity monitoring, resulting in waste accumulation problems. This study aims to design an Internet of Things (IoT)-based smart trash system with Long Range (LoRa) technology that can automatically sort waste and monitor volume to improve efficiency. Using the Research and Development (R&D) method, this system was created for automation of sorting and monitoring. The main findings show that the system successfully sorts organic and inorganic waste using proximity sensors and monitors volume with ultrasonic sensors. The system is capable of sending notifications to the Blynk dashboard via LoRa when the capacity is 95% full. LoRa testing demonstrated reliable data transmission range up to 280 meters in open areas and 30 meters in areas obstructed by walls. The system is concluded to be an effective solution for creating modern waste management through automation.